Hjernen i Immanuel Kants senværk og Cathrine Malabous samtidskritik - Larsen, Steen Nepper (Slagmark - Tidsskrift for idéhistorie, 2018)
In his late work Anthropologie in pragmatischer Hinsicht (1798), Immanuel Kant depicts the internal processes in the brain as something that cannot have the interest of a pragmatic anthropology. His profound teleology of nature does not bind the idea of man’s selfperfection to the nature of the brain. In her work Que faire de notre cerveau? (What Should We Do With Our Brain?) from 2004, Catherine Malabou argues that this question of what we should do with our brain needs a self-conscious and political answer. We can and should try to regain control of the processes that mold the cerebral constitution of man. This article discusses the arguments behind the two opposite ʻpositions’ in practical philosophy in a broader philosophical anthropological perspective. What are the limits of Kant’s approach to the brain and does Malabou’s normative project find its take-off in voluntarism?